2015
DOI: 10.1093/femsec/fiv078
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal distribution patterns of AM fungal assemblages in a Tibetan alpine grassland

Abstract: A better understanding of biogeography of Glomeromycota is essential for the conservation of arbuscular mycorrhizal (AM) fungal species and the ecosystem services that they provide worldwide. We examined the spatial dynamics of AM fungi along two slopes (4149 m a.s.l. to the summit at 5033 m a.s.l.) of Mount Mila on the Tibetan Plateau. Our hypothesis was that AM fungal communities at higher elevation would show distinct assemblages with lower diversity in conditions of increasing environmental harshness. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 60 publications
2
30
1
1
Order By: Relevance
“…4). Our results contrast with those found by Liu et al (2015) in Tibetan alpine grasslands, where the plant communities (in terms of type, cover, and density) contributed to the differences in location of the AMF communities. The present results denote a difference in AMF-community composition between sites at lower altitudes (i. e., PS and ChC) and those at the higher altitudes (i. e., CH and TH), where the environmental conditions were more extreme (e. g., a higher precipitation in the form of rain and snow).…”
Section: Discussioncontrasting
confidence: 99%
“…4). Our results contrast with those found by Liu et al (2015) in Tibetan alpine grasslands, where the plant communities (in terms of type, cover, and density) contributed to the differences in location of the AMF communities. The present results denote a difference in AMF-community composition between sites at lower altitudes (i. e., PS and ChC) and those at the higher altitudes (i. e., CH and TH), where the environmental conditions were more extreme (e. g., a higher precipitation in the form of rain and snow).…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, indicator species analyses showed that the abundance of seven OTUs (OTU3, OTU20, OTU21, OTU31, OTU35, OTU59, and OTU68) of these two families was higher at 3,600 m and 3,800 m than at 3,200 m and 3,400 m in this study. Similarly, compared with the lower elevation, Acaulospora fungi of Acaulosporaceae were relatively more abundant at higher elevation sites in Swiss Alps42 and in the Qinghai-Tibet Plateau616. In fact, Ambispora fennica , the representative species of Ambisporaceae, was initially isolated from a subarctic region in Finland (62°30′N)46, and Ambisporaceae fungi were previously found to be more abundant in higher elevation than in lower elevation regions on the Qinghai-Tibet Plateau1647.…”
Section: Discussionmentioning
confidence: 97%
“…However, as important components of soil microorganisms, arbuscular mycorrhizal (AM) fungi formed symbiotic associations with most terrestrial plant species, have shown increased, decreased, or hump-shaped diversity patterns with increasing altitude5678. This divergence in plant and AM fungal altitudinal diversity patterns may be because plant diversity is mainly determined by temperature and dispersal limitation349; in contrast, AM fungal diversity is influenced not only by plant identity and community10111213, but also by abiotic factors such as soil and climatic variables8141516.…”
mentioning
confidence: 99%
“…It also appears to be a key influence on fungal1720 and microeukaryote16 composition. In the gradient studied here, pH also appeared to influence prokaryotic composition, although not as strongly as C/N.…”
Section: Discussionmentioning
confidence: 99%